Cooperatives at Work - Cheney, George (The Future of Work Series, 2023)
Cooperatives at Work presents a range of success stories in employee ownership and worker cooperative enterprise, showcasing how such firms can embody important and highly contested ideals of democracy, equity, and social transformation